Adoption of the One Health approach to improve zoonosis control in low-income countries: Insights from the case of rabies management in Burkina Faso - Savadogo, M.; Zangré, H.; Nana, S.D.; Ilboudo, Abdoul K.; Dahourou, L.D.; Ilboudo, Guy S.; Simonis, V.; Sondo, K.A.; Akakpo, A.J.; Tarnagda, Z.; Alambedji, R.B. (Veterinary World, 2021)
Background and Aim: Rabies is a neglected zoonotic disease transmissible to humans and domestic and wild animals through biting, scratching, or licking. This study aimed to analyze the adoption of the One Health approach by the stakeholders involved in rabies control in Burkina Faso. Materials and Methods: The stakeholders involved in rabies control were from the Ministry of Livestock, Ministry of Health, Ministry of the Territory Administration, Ministry of Environment and Wildlife, and Ministry of Higher Education and Research. A structured questionnaire was used in face-to-face interviews to collect data from the stakeholders. The collected data included stakeholders’ knowledge of rabies and the One Health approach and their levels of involvement in the multisectoral collaboration. Results: Most participants could not describe rabies correctly (80%), and only 52.9% had heard of the One Health approach. In addition, there was no significant association between knowledge of rabies and participants’ characteristics, and the knowledge of the One Health approach was significantly influenced by a participant’s affiliation (place of work). Conclusion: The results call for an increase in One Health education for its effective adoption by all the rabies control stakeholders. Additional efforts should focus on continual training of the One Health workforce, from policy-makers to frontline personnel.